A Special Issue: Electric Machinery and Transformers - Huseyin R. Hiziroglu (Energies, 2023)
As the demand for electrical energy increases worldwide, engineers and scientists have been investigating new electrical systems and materials to meet this demand economically, having large-scale planning and employing environmentally friendly energy production and energy-efficient systems for consumption to minimize adverse environmental effects [...]